Characterization of Stemphylium species associated with disease of vegetable crops in Malaysia - Nasehi, Abbas (2014)
Leaf spot caused by Stemphylium spp. is one of the important diseases of vegetable crops worldwide. Forty-six isolates of Stemphylium were collected from diseased tomato (Lycopersicon esculentum L.), eggplant (Solanum melongena L.), pepper (Capsicum annuum L.) and lettuce (Lactuca sativa L.) from major vegetable production regions of Malaysia, including the states of Pahang, Johor and Selangor during 2011 - 2012. The isolates were examined based on morphological, cultural and molecular characterizations and pathogenicity. Morphological characterization revealed that the isolates were variable in color, texture, shape and pigmentation of the colonies on potato dextrose agar (PDA) and divided into 5 groups. The isolates were also variable in terms of colony size, growth rate, and size of conidia and conidiophores. Little variations were observed in the number of transvers and longitudinal septa of conidia in the isolates. The variations observed among the isolates were not correlated either to host or geographical origins of the isolates. Conidia of the isolates were similar in length, width and length/width ratio to Stemphylium solani G. F. Weber, but the isolates were also similar to S. lycopersici (Enjoji) W. Yamam. with distinct constrictions at the main transverse septa of conidia and in cultural features, particularly secretion of a yellow to dark red pigment of majority of the isolates on PDA. Various DNA regions of the isolates, including the internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (gpd), elongation factor 1-alpha protein (EF-1 alpha) and the noncoding region between the vacuolar membrane ATPase catalytic subunit A gene (vmaA) and a gene involved in vacuolar biogenesis (vpsA) regions, were compared to epitype species of the genus Stemphylium existing in the GenBank. No variation was observed among the isolates based on the four DNA regions examined and the isolates showed 100 % similarity to each other. Based on molecular analyses, the isolates associated with vegetable crops were confirmed to be S. lycopersici,and were distinguished clearly from S. solani and other Stemphylium species available in the GenBank. Pathogenicity tests revealed that all S. lycopersici isolates were pathogenic on the original hosts, namely tomato, eggplant, pepper and lettuce. However, virulence variability was observed among the isolates. This study confirmed that S. lycopersici isolates were the causal agent of leaf spot on the vegetable crops examined. In cross-inoculation assay, the representative S. lycopersici isolates selected from each crop were able to cause leaf spot on the inoculated leaves of host plants found in this study, but not on cabbage as a non-host plant. This indicated an apparent lack of host-specificity in S. lycopersici isolates on the four host crops. Genetic diversity was also assessed among 46 S. lycopersici isolates using RAPD and ISSR markers. Both RAPD and ISSR markers used to investigate the genetic variability among the isolates from the vegetable crops were able to differentiate the isolates examined. The results between the markers were congruent, however the effective multilocus marker ratio and subsequent to that the number of private alleles was greater with ISSR markers. Analysis of the genetic variation among the isolates showed significant concordance with the host plants, and no apparent geographic effect was observed. The results of the present study will provide better insight into the biology and etiology of S. lycopersici and these achievements will be helpful in the development of better disease management strategies and in the breeding of resistant varieties for vegetable production in Malaysia.